PERAN SAYYIDAH ‘AISYAH DALAM PEMBENTUKAN HUKUM ISLAM BERWAWASAN GENDER - Izzuddin, Ahmad (EGALITA, 2012)
Islamic law and women are one of mostly debated discourses bycontemporary Islamic thinkers particularly those who are gender issuesproponents. That discourse grows due to the accuse towards Islam thatthis religion is the source of gender inequality for women through outmuslim world especially in education, fairness and domestic freedom aswell as social welfare in the family. The assumption is that Islamic law ismale-based law. Therefore, it is a need to explore the note on Islamic lawdevelopment which is perceived from the role of women in the early age oflaw construction not from the aspect of the thought of classical ulama inthe middle age. This paper tries to explore and to discuss mainly the role ofSiti Aisyah as the teacher and the transmitter of hadith as the foundation ofIslamic law construction to underline women’s position and contributionas the law maker that it will prove that Islamic law is not merely men-basedlaw as the assumption grows.